Easy cleanups or forbearing improvements: The effect of CEO tenure on successor’s performance - Colak, Gonul; Liljeblom, Eva (Journal of Financial Stability, 2022)
Long CEO tenure can harm firm performance even after the CEO is replaced. We analyze this issue by conditioning post-turnover firm performance on the length of the preceding CEO’s tenure. Identification comes from instrumenting sudden CEO deaths as an exogenous shock to tenure length. We find that when a successor takes over after a long-tenured CEO, operating performance and stock returns are significantly lower, restructuring costs are higher, “big baths” are larger, and firm recovery is slower. Weaker corporate governance and a long-tenured CEO with lower skills amplify these post-turnover effects.